Sosialisasi Bayah Geopark untuk menjadi UNESCO Global Geoparks (UGG) Pada Komunitas Geopark Youth Forum (GYF) - Ahmad Fathurrozi; Prio Kustanto (Jurnal Dharmabakti Nagri, 2023)
UNESCO Global Geoparks (UGG) are single and unified geographic areas where sites and landscapes of international geological importance are managed with a holistic concept of protection, education and sustainable development. Geopark Youth Forum (GYF) is a community formed under the guidance and supervision of the Bayah Dome Geopark Management Agency, Lebak Regency, Banten Province. Its main task is to assist the Management Body in educating and promoting the Bayah Dome Geopark tourist area and managing its geosite tourism. GYF members already have the ability to use digital technology, but optimizing this digital technology to manage the tourism sector is still inadequate. This Community Service activity aims to provide socialization for GYF members to understand the concept of UGG and become the basic goal for Geopark Bayah to become part of UGG (UNESCO Global Geoparks) so that it automatically becomes a means of promoting the Geopark Bayah Dome tourism area. The hope is that the socialization of UGG will encourage enthusiasm to help manage the tourism sector so that it can improve the regional economy in a sustainable manner. Community service activities begin with the problem identification stage, discussions with partners for the preparation of work programs, implementation and evaluation. The results of the implementation of community service show that there has been an increase in understanding of the importance of Bayah Geopark being part of UGG. The results of the pre-test of the abilities of the training participants showed that as much as 100% agreed that Bayah Geopark would become part of UGG so that it would become an encouragement for this GYF in assisting tourism management at Bayah Geopark.